The Companions of the Cave in the Qur’an: A Historical and Archaeological Study - Fahmi, Muchamad Affany Syarifudin; Lubaburrahman, Muhammad Bassam; Isvani, Brian Pramudya; Rohim, Sahillah Uluwinnajah (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study explores the story of Ashabul Kahfi (the Companions of the Cave) as presented in the Qur’an, particularly in Surah Al-Kahf (verses 9–26), through historical and archaeological approaches. The story recounts a group of faithful young men who sought refuge in a cave to protect their beliefs from the threat of an oppressive ruler. This narrative conveys important values such as steadfastness in faith, monotheism, and patience in facing worldly trials. The study begins with an analysis of the Qur’anic text and classical interpretations, including those by Ibn Kathir and Al-Tabari, followed by an examination of modern literature discussing the possible location of the cave mentioned in the story. Additionally, it investigates archaeological evidence from several sites associated with Ashabul Kahfi, particularly in Jordan (the Cave of Al-Raqim) and Turkey, which continue to be subjects of scholarly debate among historians and archaeologists. The research employs a library research method, gathering data from both primary and secondary sources, including tafsir works, Islamic historical texts, archaeological reports, and international journal articles. The findings indicate that although several locations are linked to the story of Ashabul Kahfi, there is still no definitive scholarly consensus on the physical existence of the cave. Nevertheless, archaeological findings and local narratives contribute significantly to enriching the Muslim understanding of this story. This study emphasizes that the story of Ashabul Kahfi is not merely a legend or moral tale, but one with a historical dimension worthy of further investigation through scientific inquiry. By connecting sacred text, history, and archaeology, this research encourages the younger Muslim generation to approach the Qur’an’s heritage with critical and scholarly reflection, without diminishing the faith-based values it conveys.